2017
DOI: 10.1093/cid/cix860
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Acute Flaccid Myelitis Temporally Associated With an Enterovirus D68 Outbreak: Results of a Nationwide Survey of Acute Flaccid Paralysis in Japan, August–December 2015

Abstract: Fifty-nine acute flaccid myelitis cases were reported nationwide, coincident with enterovirus D68 (EV-D68) outbreak from August to December 2015. Strong temporal association was noted, and EV-D68 was detected from some cerebrospinal fluid and blood specimens. Antiganglioside antibodies were identified in some patients, and prognostic factors were analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
122
1
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 105 publications
(133 citation statements)
references
References 33 publications
(39 reference statements)
8
122
1
2
Order By: Relevance
“…9 In contrast to previously reported US cohorts, our patients were notably younger, with a median age at onset of 4 years compared with the California and Colorado reports where the median age at onset was 7 years but similar to the recently described Japanese cohort. 2,9 New in this series, we present quantitative clinical and imaging profiles that may help distinguish AFM from other myelopathies also presenting in childhood, especially inflammatory myelopathies (e.g. demyelinating, autoimmune, or postinfectious) and spinal cord ischaemia.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…9 In contrast to previously reported US cohorts, our patients were notably younger, with a median age at onset of 4 years compared with the California and Colorado reports where the median age at onset was 7 years but similar to the recently described Japanese cohort. 2,9 New in this series, we present quantitative clinical and imaging profiles that may help distinguish AFM from other myelopathies also presenting in childhood, especially inflammatory myelopathies (e.g. demyelinating, autoimmune, or postinfectious) and spinal cord ischaemia.…”
Section: Discussionsupporting
confidence: 68%
“…2,18 At this time, no causal link implicating EV-D68 as the aetiological agent for AFM has been established. Current evidence rests on a temporal association between cases and an epidemiological rise in community cases, 9 EV-D68 detection mostly in nasopharyngeal secretions in a small percentage of AFM cases and exclusion of other infectious aetiologies, including poliovirus and West Nile virus. 9,10 Of note, also in the AFM temporal profile is the hyperacute onset of neurological symptoms reaching nadir within 6 hours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we administered intravenous immunoglobulin for AFM or GBS. In 2015, a series of AFM cases were reported, which prompted us to suspect AFM in this case .…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Previous studies have shown that the peak incidences of AFM and severe respiratory illness coincide. 5 In Japan, an EV-D68 outbreak occurred in the autumn of 2015 in association with a cluster of AFM cases 6 and an increased level of severe respiratory illness. 7 The outbreak first presented as increased numbers of children with severe respiratory illness and / or asthma exacerbation.…”
mentioning
confidence: 99%